The Relationship between Husband's Support and Postpartum Blues in Pregnant Women at Sibuhuan General Hospital - Tamba, Fauji Haryati; Hutasuhut, Rina Marlina (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2024)
Support is encouragement in the form of comfort, care, appreciation, or assistance available to an individual from another person or group. Support can be obtained from a number of important people such as husband, children, parents, siblings or relatives and close friends. Husband's support has dimensions, namely instrumental support, emotional support, appreciation support, and information support. Postpartum mothers are at risk for changes in mood or mood disorders, namely postpartum blues. Among the factors that cause postpartum blues is lack of husband's support. Objective: To determine the relationship between husband's support and the occurrence of postpartum in mothers. Method: This research uses quantitative descriptive with a cross sectional approach. The sample size used was 100 postpartum mothers at the RSUD Sibuhuan Hospital and the Permata Madina Hospital using simple random sampling. This research used a husband's support questionnaire and EPDS. Data analysis used the chi-square statistical test with a significant value of p: 0.05 using SPSS 25. Results: The research results showed that p = 0.19, which shows that there is a relationship between husband's support and the occurrence of postpartum blues in mothers. Mothers who do not experience postpartum blues tend to have strong husband support. Conclusion: Further research is needed to find out the main causes of mothers experiencing postpartum blues